A rigorous process modeling methodology for biomass fast pyrolysis with an entrained‐flow reactor. Issue 1 (29th August 2019) - Caudle, Benjamin H.; Gorensek, Maximilian B.; Chen, Chau‐Chyun
Abstract: A biomass fast pyrolysis model was developed for implementation in equation‐oriented modeling software. Based on a previous framework of coupled 1‐dimensional mass, momentum, and heat balance equations, this model includes updated reaction kinetics to provide a more detailed representation of biomass components, intermediates, and products. A recently published derivation of thermodynamic properties for the species in this model has allowed the energy balance around the pyrolysis reactor to be rigorously redefined. With these improvements, the optimum pyrolysis temperature for bio‐oil production predicted by the model is increased by up to 50°C, bringing it in line with experimental data and increasing the overall agreement. More importantly, the reactor energy balance is strictly enforced. The resulting model can be used for the design and optimization of biomass fast pyrolysis processes, and comparisons with other options for biomass utilization. Abstract : A biomass fast pyrolysis process model, including reactor, separations, and heat recovery, is presented for ready implementation in commercially available process simulation software. The one‐dimensional entrained‐flow reactor model imposes a rigorous energy balance, providing estimation of temperature profiles, energy utilization, and energy efficiency. Updated reactions and component properties allow for an accurate first principles approach to modeling a wide variety of process conditions and biomass feedstocks.